Enhancing Organisational Citizenship Behavior: A Trust-Based Perspective on Leadership and Support - Sambudi Hamali; Ridho Bramulya Ikhsan; Calvin Lucky Efendi; M Rhido (International Journal of Business Economics (IJBE), 2025)
Purpose – This research examines the impact of transformational leadership, perceived organisational support, and organisational trust on organisational citizenship behaviour among Generation Z employees working in DKI Jakarta and tests organisational trust as a mediating variable.Methodology – This study employs a quantitative approach, specifically a causal study design utilising non-probability sampling. Data were gathered from 134 Generation Z respondents working in companies within DKI Jakarta through a questionnaire distributed via Google Forms. The data analysis used is the Structural Equation Model SEM-PLS with Warppls 8.0 software.Findings – The results showed that transformational leadership, perceived organisational support, and organisational trust affect organisational citizenship behaviour. Transformational leadership is more dominant in influencing organisational citizenship behaviour. Organisational trust as a mediating variable of the relationship between transformational leadership and perceived organisational support on organisational citizenship behaviour.Originality/Novelty – This study examined the influence of transformational leadership, perceived organisational support, and organisational trust on organisational citizenship behaviour, in contrast to previous studies that examined these factors separately. It also examined organisational trust as a mediating variable in the relationship between transformational leadership, organisational support, and organisational citizenship behaviour.Implications – Companies in DKI Jakarta must build trust between leaders and Generation Z with wise and inclusive leadership. In addition, leaders must be role models, inspire, and foster pride in the team.